Impacts of Export Restrictions on the Global Personal Protective Equipment Trade Network During COVID‐19 (Adv. Theory Simul. 4/2022). Issue 4 (11th April 2022) - Ye, Yang; Zhang, Qingpeng; Cao, Zhidong; Chen, Frank Youhua; Yan, Houmin; Stanley, H. Eugene; Zeng, Daniel Dajun
Abstract : Impacts of Export Restrictions on the Global Personal Protective Equipment Trade Network During COVID‐19 In article number 2100352, Ye, Zhang and co‐workers investigate the effect of personal protective equipment (PPE) shortages on COVID‐19 contagion patterns. Integrating a metapopulation model and a threshold model, it is found that export restrictions on PPE cause shortage contagion on the global PPE trade network to transmit even faster than the disease contagion on global mobility network.